2019
DOI: 10.1021/acs.cgd.9b00503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Ions on the Crystal Growth Kinetics and Microstructure of Calcium Carbonate

Abstract: In the present work, calcium carbonate was precipitated at 28 °C in the presence of iron ions using an accelerated scale method based on CO2 repelling from the solution. The polymorphism and morphology of the obtained precipitates were investigated using scanning electron microscopy, X-ray diffraction, and Fourier transform infrared analyses. At high solution supersaturations, iron ions did not have a significant effect on the inhibition of calcium carbonate crystallization. However, at relatively low solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…This agrees with the results of Korchef [16] who showed that vaterite was the predominant polymorph at 28°C, for a supersaturation in the range 4-14, and calcite was not detected, because of the low initial calcium concentration (4 Â 10 À3 M). Thus, for a solution supersaturated with respect to calcite ($15-62), aragonite (4-17) and vaterite , vaterite was favored for an initial calcium concentration 4 Â 10 À3 M(<10 À2 M), a precipitation pH in the range 8.4-8.8 and a temperature of 28°C [16]. [36]).…”
Section: Effect Of Operating Parameters On Caco 3 Precipitationsupporting
confidence: 92%
See 4 more Smart Citations
“…This agrees with the results of Korchef [16] who showed that vaterite was the predominant polymorph at 28°C, for a supersaturation in the range 4-14, and calcite was not detected, because of the low initial calcium concentration (4 Â 10 À3 M). Thus, for a solution supersaturated with respect to calcite ($15-62), aragonite (4-17) and vaterite , vaterite was favored for an initial calcium concentration 4 Â 10 À3 M(<10 À2 M), a precipitation pH in the range 8.4-8.8 and a temperature of 28°C [16]. [36]).…”
Section: Effect Of Operating Parameters On Caco 3 Precipitationsupporting
confidence: 92%
“…Several techniques, such as mechanical stirring [29], aeration [30], electrochemical precipitation [31], magnetic water treatment [32] have been used in laboratories to assess the effectiveness of chemical or physical treatment, and the influence of certain parameters on scale formation over time. However, the most interesting method used for CaCO 3 precipitation is the CO 2 repelling method [16,17,33] where the CO 2 containing solution is air bubbled which increases the solution pH and provokes the CaCO 3 precipitation (Figure 3). Indeed, this method is an accelerated simulation of the natural scaling phenomenon in which the precipitation of CaCO 3 takes place, in a short experiment time that do not exceed 90 min, following the removal of the dissolved CO 2 by the atmospheric air, according to the following reaction [16,17]:…”
Section: System Caco 3 -H 2 O-comentioning
confidence: 99%
See 3 more Smart Citations